Effect of Harvest Maturity and Pre-cooling on Post Harvest Rots of Apple - Kumari, Neelam; Sharma, J. N.; Singh, Deepika (International Journal of Economic Plants, 2019)
The effects of harvest maturity and different post harvest pre-cooling methods on post harvest rotting of apple fruits were studied. The apple fruits picked later (126 DFFB) were more sensitive to rot with mean rot of 76.21%. Early harvesting (106 DFFB) significantly resulted in minimum rotting of fruits (12.81%). Pre-cooling treatment with HIWC (ice water and calcium chloride) for 30 min was found most effective among all other cooling medium. Minimum fruit rot (4.69%) was recorded in the fruits pre-cooled with HIWC followed by RC (refrigerated cooling) (6.81%) and HIW (ice water) (7.03%), respectively.